It's Not a Lie If You Believe the Norm Does Not Apply: Conditional Norm-Following with Strategic Beliefs - Cristina Bicchieri; Eugen Dimant; Silvia Sonderegger (Center for Economic Studies and ifo Institute (CESifo), 2020)
We experimentally investigate whether individuals strategically distort their beliefs about dominant norms. Embedded in the context of lying, we systematically vary both the nature of elicited beliefs (descriptive about what others do, or normative about what others approve of) and whether subjects are aware of the forthcoming lying opportunity at the belief-formation stage. We build a dual-self model of belief distortion applied to the context of social norms and derive a number of precise predictions. Our findings provide a perspective on why, when and which norm-relevant beliefs are strategically distorted and show that not all belief distortions are created equal.
Keywords: C72; C91; D80; D90; 330; lying; social norms; strategic beliefs; uncertainty